Structural studies of insect cytokine-like stress responsive peptide 4 - Miller, Hannah (Kansas State University, 2023)
Similar to innate immunity in vertebrates, insects rely on a variety of both humoral and cellular responses to defend themselves from pathogen invasion. A family of peptides has been identified in the hemolymph of six orders of insects that function like cytokines to regulate immune responses. This family of peptides is activated during times of stress - such as pathogen invasion, wounding, and heat or cold shock – and are rightfully named Stress Responsive Peptides (SRPs). The SRP family plays a variety of roles within the insect immune system making each of their structure-activity relationships compelling. Mature Manduca Sexta Stress Responsive Peptide-4 (SRP-4) is a 26-residue peptide stabilized with a disulfide bond between residues 7C and 18C. Its structure was investigated through 2D ¹H-¹H Nuclear Magnetic Resonance (NMR) Spectroscopy and Nuclear Overhauser Effect (NOE) derived constraints. We observed that SRP-4 contains two short beta strands between residues 10G-12V and 15G-18C, which are connected by a beta-turn. The N- and C-termini of SRP-4 are intrinsically disordered. SRP-4 bears structural similarity to the previously studied SRP-1 and -2. The structural studies of this peptide also revealed a resemblance to the C-terminal subdomain of the human epidermal growth factor (EGF). The solved structure of this peptide within the stress responsive peptide family aids in our understanding of their unique roles in the immune system.
Keywords: Stress responsive peptide; Insect cytokine; Insect immunity; Nuclear magnetic resonance